Biologically Safe, Versatile, and Smart Bismuthene Functionalized with a Drug Delivery System Based on Red Phosphorus Quantum Dots for Cancer Theranostics. Issue 22 (31st March 2022) - Song, Huaibing; Wang, Jun; Xiong, Bin; Hu, Jiayuan; Zeng, Pei; Liu, Xiaoming; Liang, Huageng
Abstract: Two‐dimensional nanomaterials are attracting attention for cancer therapy. However, high toxicity, insensitivity to external stimuli and single therapeutic modality are still key issues hindering their clinical application. Therefore, the construction of a safe, intelligent and versatile nanocomposite is needed to meet clinical expectations. Herein, we developed a nanocomposite of Bi@RP‐PEG‐DOX with 2D bismuthene loaded with 0D red phosphorus quantum dots and DOX. The nanocomposite with DOX loading capacity (ca. 250 %) and photothermal conversion efficiency (ca. 54 %) showed both photothermal and photodynamic effects and a sensitive response of drug release to the acidic tumor microenvironment or NIR II laser irradiation. The nanocomposite exhibits good biosafety. Through the X‐ray attenuation properties of bismuth, the nanocomposite serves as an excellent CT contrast agent, providing potential to perform CT‐guided therapy. Abstract : A bismuthene‐loaded red phosphorus quantum dot (BP QD)‐ and DOX‐based drug delivery system was constructed that is biologically safe, versatile, and exhibits smart light‐ and pH‐responsiveness. The material showed an extremely high drug loading capacity (ca. 250 %) and excellent photothermal conversion efficiency (ca. 54 %). The intrinsic photothermal properties of bismuthene and photodynamic effects of RP QDs enhanced the antitumor activity.